Seeking Convergence? A Comparative Analysis of the Jurisprudence of the European Court of Human Rights and the Court of Justice of the European Union on Seeking Asylum - Łysienia, Maja (sui generis Verlag, 2022)
Since 2009 two courts have been shaping human rights of asylum seekers in Europe: the Court of Justice of the EU (CJEU) and the European Court of Human Rights (ECtHR). Side by side, the courts examined who is protected from refoulement, when and how asylum seekers can be detained and what remedies they should have access to. Did they seek convergence in their asylum case-law or paid no attention to each other's jurisprudence? Did they establish a coherent standard of the asylum seekers' protection in Europe? Judicial dialogue between the ECtHR and CJEU in the area of asylum is at the heart of this study. The book offers also a comprehensive overview of the asylum case-law of the two courts and identifies the main convergences and divergences in their approach to protection against refoulement, immigration detention and effective remedies.